ダイ 30 ジ ナンキョク チイキ カンソク タイ アスカ カンソク キョテン エットウ タイ (1989) チュウクウ ケイ ホウコク - 行松, 彰; ユキマツ, アキラ; Yukimatu, Akira (1992)
P(論文) この報告は, 第30次南極地域観測隊あすか観測拠点越冬隊宙空部門が, 1989年1月1日から同年12月24日まで, あすか観測拠点において行った超高層研究観測に関するものである。あすか観測拠点では越冬3年目の30次で初めて宙空系隊員1名が越冬することになり, 28,29次の観測を引き継ぐとともに, 新たな観測機器を導入し, 本格的な越高層観測を開始した。観測に関して特記すべきことは, 以下の7点である。1) 30MHzリオメーターを設置し, 通年観測を行った。2) 固定方位及びトラッキングフォトメーターを新設して初めて通年観測を行った。3) 28次持ち込み(かつ持ち帰った)全天カメラを一部改良して持ち込み, 観測した。4) 全天SIT-TVカメラを新設し観測を行った。5) 新たにディジタルデータレコーダーを追加してデータ取得を確実なものとした。6) ULF磁力計のZ成分の故障を修復し, 観測を復活した。7) 太陽活動度が最大級であったため, 興味深い多くの地球電磁気学的現象が観測された。 This paper describes observations of the upper atmosphere physics at Asuka Station from January 1 to December 24,1989,carried out by the 30th Japanese Antarctic Research Expedition (JARE-30). In JARE-30 one research member of the upper atmosphere physics has been wintering at Asuka Station, and several instruments were newly installed so as to observe auroral phenomena in conjunction with Syowa Station, Iceland observations, and scientific satellites. Characteristics of the JARE-30's observations at Asuka Station are as follows : 1) The observation of CNA with a 30-MHz riometer has been made throughout the year. 2) A fixed direction and a tracking photometers were newly installed, and spatial and temporal developments of aurora photo emissions in various wave lengths were observed. 3) An all sky camera used in JARE-28 was re-installed. 4) An all sky SIT-TV camera was newly installed so as to observe auroral motions with high time resolution. 5) A digital data recorder was installed for the auroral photometric data. 6) Z-component of a ULF induction magnetometer which had been in trouble was recovered, so we could observe the three components of both a fluxgate magnetometer and the induction magnetometer. 7) In 1989,the solar activity was very high and there were many interesting geophysical events, and auroral phenomena. departmental bulletin paper